Baamboozle media effect of the student's interest and cooperative accounting learning outcomes - Novi Tri Wulandari; Supri Wahyudi Utomo; Farida Styaningrum (Assets: Jurnal Akuntansi dan Pendidikan, 2025)
In the digital era, student interest and learning outcomes need to be improved through innovative and interactive learning media. However, at SMKN 5 Madiun, traditional media still dominates, making students passive and unmotivated. This study aims to analyze the role of Baamboozle learning media in improving student interest and learning outcomes in Cooperative Accounting at SMKN 5 Madiun. The results show that the use of Baamboozle media has a significant effect of increasing student learning interest. The interactive and entertaining learning approach can encourage active student involvement during the learning process, thus creating a more interesting and participatory learning atmosphere. However, the effect of Baamboozle on student learning outcomes shows a lower level of significance compared to its effect on learning interest. Nevertheless, the positive contribution of Baamboozle media remains relevant in supporting the improvement of learning quality, particularly in helping students understand accounting concepts. Based on these findings, students are expected to be more actively involved in the learning process by utilizing the available interactive features.